Evidence of the need for developing an integrated model of mathematics teachers' readiness as agents of change - Talib, Sharida Abu; Nasri, Nurfaradilla Mohamad; Mahmud, Muhammad Sofwan (Journal of Education and e-Learning Research, 2024)
This study aims to identify the need to develop an integrated model of the readiness of mathematics teachers as agents of change. Teachers' readiness is crucial for the effectiveness of the teaching process and the enhancement of pedagogical innovation. This study employs a qualitative methodology. A semi-structured interview was conducted with 14 study participants to ensure that the proposed model fits the demands of users. This includes education and teaching experts from Malaysia’s southern and central regions. The interview data were transcribed and analyzed thematically using ATLAS.ti24 software. Results indicate a need to develop an integrated model of mathematics teachers' readiness as agents of change. All study participants emphasized the significance of addressing mathematics teacher readiness. Three main themes have been identified: (1) pedagogical needs, (2) strengthening mathematics teacher competence and (3) the configuration model as a guideline and checklist. The findings emphasize the importance of addressing mathematics teachers' readiness. An integrated model based on professional knowledge and pedagogical skills was proposed to support teachers in acting as agents of change. This study provides valuable insights for mathematics teachers and stakeholders. The findings indicate directions for future research particularly in the systematic development and design of the proposed integrated model which aims to enhance teacher readiness and pedagogical innovation.